2011
DOI: 10.1152/physiol.00020.2011
|View full text |Cite
|
Sign up to set email alerts
|

Why is Chromosome Segregation Error in Oocytes Increased With Maternal Aging?

Abstract: It is well documented that female fertility is decreased with advanced maternal age due to chromosome abnormality in oocytes. Increased chromosome missegregation is mainly caused by centromeric cohesion reduction. Other factors such as weakened homologous recombination, improper spindle organization, spindle assembly checkpoint (SAC) malfunction, chromatin epigenetic changes, and extra-oocyte factors may also cause chromosome errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 133 publications
0
24
0
Order By: Relevance
“…It is estimated that 20% of human oocytes are aneuploid, and mistakes in meiotic chromosome segregation account for one third of all pregnancy losses (Hassold and Hunt, 2001;Qiao et al, 2014;Wang et al, 2011). Both MI and MII exits are key events in maintaining the euploidy of oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 20% of human oocytes are aneuploid, and mistakes in meiotic chromosome segregation account for one third of all pregnancy losses (Hassold and Hunt, 2001;Qiao et al, 2014;Wang et al, 2011). Both MI and MII exits are key events in maintaining the euploidy of oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage at telomeres could contribute to telomere attrition, contributing to non-disjunction, miscarriage and Downs syndrome [14][15][16]. Old mouse oocytes show shorter telomeres than those of young oocytes [17].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Previously, we and others have fully reviewed the cellular and molecular alterations as well as the mechanisms underlying oocyte aging [1, 2,6,7]. The protein profiles during porcine oocyte aging have also been investigated by us [30].…”
Section: Special Topicmentioning
confidence: 99%
“…It has been well established that a decline in female fertility with increasing maternal age is due to high frequency of errors in meiotic chromosome segregation during female meiosis [1,2]. Studies suggested that defects in deacetylation at some histone lysine residues in old oocyte may be involved.…”
Section: Epigenetic Changes: Underlying Mechanisms Of Oocyte Agingmentioning
confidence: 99%
See 1 more Smart Citation